Operation of LED Light as Emergency Lighting Resource DC with Charger Control Based Arduino Uno ATmega - Rinas, I Wayan; Suartika, I Made; Pemayun, Anak Agung Maharta; Raka Agung, I G. A. P. (Journal of Electrical, Electronics and Informatics; Vol 1 No 2 (2017): JEEI (September 2017)DO - 10.24843/JEEI.2017.v01.i02.p04, 2017)
Lighting is very important to support the activities of human life. To maintain the continuity of lighting can use power source from genset or battery. Now many manufactured LED (light emitting diode) bulb type which is energy saving with life time up to 50.000 hours. LEDs of this type can be operated with AC and DC current. The design control charger based Arduino Uno ATmega micro controller is used as a control system for charging and turning on LED lights. In this research the measurement of light intensity is done at 220 volt AC as reference, then measured the intensity of light for operation on some variation of DC voltage. The measurement results at DC voltage, LED Osram can be operated at 115 volt DC has reached the same light intensity with 220 volt AC. This selection aims to reduce the amount of battery usage as a DC power source.